Untypical bilateral breast cancer with peritoneal fibrosis on 18F-FDG PET/CT: case report and literature review - Song, Lele; Qiu, Yongkang; Huang, Wenpeng; Sun, Xinyao; Yang, Qi; Peng, Yushuo; Kang, Lei (Frontiers in Medicine, 2024)
Background: Retroperitoneal fibrosis, a condition of uncertain origin, is rarely linked to 8% of malignant cases, including breast, lung, gastrointestinal, genitourinary, thyroid, and carcinoid. The mechanism leading to peritoneal fibrosis induced by tumors is not well understood, possibly encompassing direct infiltration of neoplastic cells or the initiation of inflammatory responses prompted by cytokines released by tumor cells. We report a case of breast cancer with renal metastasis and retroperitoneal fibrosis detected by 18 F-FDG PET/CT, providing help for clinical diagnosis and treatment.Case Report: A 49-year-old female was referred to the hospital with elevated creatinine and oliguria for over a month. Abdominal computer tomography (CT) and magnetic resonance imaging (MRI) showed a retroperitoneal fibrosis induced acute kidney injury (AKI) was suspected. However, a percutaneous biopsy of the kidney lesion confirmed metastasis from breast cancer. The physical examination revealed inverted nipples and an orange peel appearance on the skin of both breasts.Ultrasonography revealed bilateral hyperplasia (BIRADS 4a) of the mammary glands and bilateral neck and axillary lymphadenopathy. Subsequently, 18F-FDG PET/CT detected abnormally high uptake (SUVmax) in the bilateral mammary glands and axillary lymph nodes, suggesting bilateral breast cancer. Further, abnormal 18 F-FDG uptake was detected in the kidney, suggesting renal metastasis. In addition, abnormal 18 F-FDG uptake was observed in the vertebrae, accompanied by an elevation in inhomogeneous bone mineral density, prompting suspicion of bone metastases. However, the possibility of myelodysplasia cannot be dismissed, and we will look further in close follow-ups. There was significant 18 F-FDG uptake in the retroperitoneal position, suggesting a potential relationship between retroperitoneal fibrosis and breast cancer. The final pathological diagnosis of the breast tissue confirmed bilateral invasive ductal carcinoma. The patient had been treated with 11 cycles of albuminbound (nab)-paclitaxel (0.3 mg) and had no significant adverse reaction.In this case, neither the bilateral breast cancer nor the kidney metastatic lesion showed typical nodules or masses, so breast ultrasound, abdominal CT, and MRI did not suggest malignant lesions. PET/CT played an important role in detecting occult metastases and primary lesions, thereby contributing to more accurate staging, monitoring treatment responses, and prediction of prognosis in breast cancer.